Race/Ethnicity as a Predictor for Location of Death in Patients With Acute Neurovascular Events. (January 2018) - Salomon, Say; Chuang, Elizabeth; Bhupali, Deepa; Labovitz, Daniel
Background: Site of death is an important quality indicator for patients with terminal illness. Racial and ethnic disparities exist in the quality of end-of-life care. This study explores the site of death of patients admitted for and dying of complications of acute neurovascular events in a hospital network in an urban, low-income, predominantly minority community. Methods: This is a retrospective cohort study of patients admitted to 1 of 3 general hospitals that are part of an academic medical center in Bronx, New York, with the diagnosis of acute ischemic stroke, intracerebral hemorrhage, or subarachnoid hemorrhage who died during the index admission or were discharged with hospice services. The main outcome was location of death (palliative care inpatient unit [IPU] at the medical center or hospice services at discharge vs death on any other IPU). Results: A total of 655 patients admitted with acute neurovascular events from January 1, 2009, to March 1, 2015, died or were discharged with hospice services and were included in the analysis. Of those patients, 238 (36.3%) were black, 233 (35.5%) were Hispanic, and 184 (28.1%) were white. A total of 178 (24.4%) died on the palliative care unit or were discharged with hospice services, including 55 black patients (23.1%), 52 (28.3%) white patients, and 53 (22.7%) Hispanic patients. These differences were not statistically significant, even when controlling for confounders. Conclusion: This study did not show a difference in site of death in our institution by race or ethnicity, which is considered an important quality end-of-life care metric.